Experimental and thermodynamic study on sorption-enhanced steam reforming of toluene for H2 production using the mixture of Ni/perovskite-CaO. (1st December 2021) - Zhang, Zhonghui; Qin, Changlei; Ou, Zhiliang; Xia, Hongqiang; Ran, Jingyu; Wu, Chunfei
Highlights: Toluene steam reforming to H2 with in-situ CO2 capture by Ni/Perovskite and CaO. Understanding the key roles of S/C ratio and temperature during SESR of toluene. Achievement of 90% hydrogen yield with a fraction of maximum 95% under 650 °C. Good compatibility of Ni/Perovskite catalyst and CaO sorbent in SESR of toluene. Abstract: It is known that a considerable amount of tar is usually generated in the biomass gasification process, and catalytic steam reforming is an effective method to remove this by-product. The coupling of in-situ CO2 capture in the process can further shift the forward reforming reaction and produce hydrogen with a high purity. In this work, sorption enhanced steam reforming (SESR) of toluene (as a model compound of biomass tar) was investigated thermodynamically and experimentally using the mechanically mixed Ni/perovskite catalyst and CaO sorbent. It is verified that the appropriate temperature is 650 °C under stoichiometric reaction (S/C = 2), and around 75% average H2 yield with a maximum H2 purity over 95% could be obtained. Moreover, the cyclic SESR-regeneration and characterization including XRD, SEM/EDS, TEM and XPS were carried out, and it shows a stable catalytic performance and compatibility of the Ni/perovskite catalyst in the SESR process for high-purity hydrogen production.